NF45/NF90-mediated rDNA transcription provides a novel target for immunosuppressant development - Tsai Hsiang-Tsai; Zeng Xiaobin; Liu Longshan; Xin Shenchang; Wu Yingyi; Xu Zhanxue; Zhang Huanxi; Liu Gan; Bi Zirong; Su Dandan; Yang Ming; Tao Yijing; et al. (WILEY, 2022)
Herein, we demonstrate that NFAT, a key regulator of the immune response, translocates from cytoplasm to nucleolus and interacts with NF45/NF90 complex to collaboratively promote rDNA transcription via triggering the directly binding of NF45/NF90 to the ARRE2-like sequences in rDNA promoter upon T-cell activation in vitro. The elevated pre-rRNA level of T cells is also observed in both mouse heart or skin transplantation models and in kidney transplanted patients. Importantly, T-cell activation can be significantly suppressed by inhibiting NF45/NF90-dependent rDNA transcription. Amazingly, CX5461, a rDNA transcription-specific inhibitor, outperformed FK506, the most commonly used immunosuppressant, both in terms of potency and off-target activity (i.e., toxicity), as demonstrated by a series of skin and heart allograft models. Collectively, this reveals NF45/NF90-mediated rDNA transcription as a novel signaling pathway essential for T-cell activation and as a new target for the development of safe and effective immunosuppressants.